Cation-directed enantioselective N-functionalization of pyrroles - Armstrong, R; D'Ascenzio, M; Smith, M (Thieme Publishing, 2016)
A catalytic enantioselective N-functionalization of pyrroles has been developed. Imines formed in situ via condensation underwent cation-directed cyclization with complete N-regioselectivity. The cyclized products were obtained with enantiomeric ratios up to 96:4 for aldimine substrates and up to 99:1 for trifluoromethyl ketimines. The reaction proceeds without an acidifying group on the pyrrole and offers a new approach to the generation of chiral nonracemic aminals.